Financial Behavior as a Mediator of Islamic Financial Literacy and Fintech Experience - Aris Mizar; Surna Lastri; Nuzulman (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study analyzes the mediating role of financial behavior in the relationship between Islamic financial literacy and fintech experience on the financial well-being of university students in Banda Aceh. Using a quantitative approach, data were collected through a structured survey involving 395 active students and analyzed using Structural Equation Modeling (SEM-AMOS). The findings show that Islamic financial literacy and fintech experience have significant direct and indirect effects on financial well-being, with financial behavior functioning as a strong mediator. Students with higher Islamic financial literacy tend to demonstrate more prudent, ethical, and Sharia-compliant financial actions that contribute to better financial outcomes. Meanwhile, extensive fintech experience enhances efficiency in financial management, yet its impact becomes optimal only when accompanied by disciplined financial behavior. The integrated model developed in this study successfully explains 80.6% of the variation in students’ financial well-being, indicating the strong influence of cognitive, experiential, and behavioral factors compared to demographic variables. These results highlight the importance of strengthening financial education, particularly by combining Islamic financial principles with digital financial literacy, to support students in navigating financial challenges in the digital era. The study also provides implications for educators, policymakers, and fintech providers in designing targeted interventions that promote responsible financial practices among young adults.